Qualitative and Quantitative Analysis of Lecithin Content and Bioactive Chemical Compenents of Corn Oil From Dompu District - Ramadhan, M. Kaisar Sutomo; Permadi, Adi; Sulistiawati, Endah (Jurnal Biologi Tropis, 2024)
Indonesia is one of the Asian nations that has an abundance of vegetation that can be utilized as food yields and medication. One of the plants that can be utilized as neighborhood food is the Corn plant (Zea mays L.), corn is one kind of food crop that has for some time been known and developed. Dompu Regency, located in the province of West Nusa Tenggara,  is one of the largest corn producers in Indonesia. From this statement, a revolution is needed for the development of the food industry sector, namely the development of processed products from corn raw materials, namely corn oil. Corn oil extraction is carried out by the Maceration Method, a simple extraction process carried out by soaking the simplicia in a solvent for a certain time at room temperature and protected from light. Development in finding the percentage level (%) of lecithin LC-HRMS (Liquid Choromatography High-Resulution Mass Spectrometry), Among the Compounds: Percentage level (%) of bioactive lecithin compounds from major (main) components: 1-[(11Z)-octadecenoyl]-sn-glycero-3-phosphocholine (C26H52NO7P) = 8.882%, 1-Linoleoyl-2-Hydroxy-sn-glycero-3-PC (C26H50NO7P) = 6.874%, 1 Palmitoy-Phospadicholine (C24H50NO7P) = 1.898%, 1-Oleoyl-2-hydroxy-sn-glycero-3-PE (C23H46NO7P) = 1.161%, 2-monolinolenin (C21H36O4) = 0.577, (2R)-2-Hydroxy-3-(phosphonooxy)propyl (11Z,14E)-11,14-icosadienoate (C23H43O7P) = 0.386 %, 1-Stearoylglycerol (C21H42O4) = 0.072.